Access to medications for opioid use disorder for formerly incarcerated individuals during community reentry: a mini narrative review - Jason S. Chladek; Michelle A. Chui; Michelle A. Chui (Frontiers Media S.A., 2024)
Medications for opioid use disorder (MOUD) are especially important for formerly incarcerated individuals with opioid use disorder (OUD) and can reduce the risk of re-arrest and overdose during community reentry. Unfortunately, few formerly incarcerated individuals are able to access MOUD within the community, missing a critical tool for rehabilitation. A mini narrative review was conducted to highlight the published work that has been done to improve access to MOUD for formerly incarcerated individuals during reentry. The results yielded 15 records describing intervention evaluations, program descriptions, and research in progress. Most work is ongoing, showing promise that researchers have identified the importance of this problem. However additional research should be done to include other stakeholders and address the limitations of existing interventions and programs. Continued efforts can help ensure that formerly incarcerated individuals can safely and successfully reintegrate into society.